O petróleo e a crise econômica venezuelana : impactos sócioeconômicos na zona de fronteira Brasil-Venezuela no período de 2008 à 2015 - Carvalho, Reginaldo Pereira de (2017)
This dissertation assesses the impacts of the political and economic crisis that hit Venezuela during the period 2008 to 2015, triggered by the fall in the international price of oil, the main product of the country's economy, and its developments on border and Trade relations between Brazil and Venezuela, with emphasis on the socioeconomic impacts produced in the border region between the two countries, more particularly in the zone of border influence located between the north of the state of Roraima and the south of the state of Bolivar. In this period, due to the sharp drop in the international price of oil, Venezuela faces a sharp contraction in economic activity that intensifies the political dispute between government and opposition, confronting the state-based national economy projects implemented by Hugo Chávez and continued by Nicolás Maduro, and the project of liberal economy, defended by oppositionists, where diverse economic mechanisms are used by both sides as instruments of defense of their interests. The political instability of the country and the insecurity of its market cause reduction of investments, capital flight, crisis of exchange and crisis of shortage. These factors profoundly affect the economic relations between the two countries both at the national level and particularly in the border area inhabited between them, resulting in the emergence of new ones and the aggravation of old social problems that already reached the frontier region.